Ask Question
29 November, 06:34

3 (n-1) = 6 what is the answer

+2
Answers (1)
  1. 29 November, 08:04
    0
    Simplifying

    3 (n + - 1) = 6

    Reorder the terms:

    3 (-1 + n) = 6

    (-1 * 3 + n * 3) = 6

    (-3 + 3n) = 6

    Solving

    -3 + 3n = 6

    Solving for variable 'n'.

    Move all terms containing n to the left, all other terms to the right.

    Add '3' to each side of the equation.

    -3 + 3 + 3n = 6 + 3

    Combine like terms: - 3 + 3 = 0

    0 + 3n = 6 + 3

    3n = 6 + 3

    Combine like terms: 6 + 3 = 9

    3n = 9

    Divide each side by '3'.

    n = 3

    Simplifying

    n=3
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “3 (n-1) = 6 what is the answer ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers